2007
DOI: 10.1038/nrn2154
|View full text |Cite
|
Sign up to set email alerts
|

Recognition memory and the medial temporal lobe: a new perspective

Abstract: Recognition memory is widely viewed as consisting of two components, recollection and familiarity, which have been proposed to be dependent on the hippocampus and the adjacent perirhinal cortex, respectively. Here, we propose an alternative perspective: we suggest that the methods traditionally used to separate recollection from familiarity instead separate strong memories from weak memories. A review of work with humans, monkeys and rodents finds evidence for familiarity signals (as well as recollection signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

47
809
15
5

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 881 publications
(907 citation statements)
references
References 121 publications
47
809
15
5
Order By: Relevance
“…Consequently, any account of diencephalic mechanisms supporting recognition memory must be able to explain this asymmetric relationship. As already explained, this dissociation poses problems for single-process models of recognition memory (Squire et al 2007). 5.…”
Section: Toward a Model Of Diencephalic Contributions To Recognition mentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, any account of diencephalic mechanisms supporting recognition memory must be able to explain this asymmetric relationship. As already explained, this dissociation poses problems for single-process models of recognition memory (Squire et al 2007). 5.…”
Section: Toward a Model Of Diencephalic Contributions To Recognition mentioning
confidence: 99%
“…This arrangement ensures that medial temporal structures such as the perirhinal cortex and hippocampus are ideally placed to detect rapidly the repeat occurrence of an event and then initiate appropriate brain responses (Brown and Aggleton 2001;Diana et al 2007;Eichenbaum et al 2007;Squire et al 2007). Once the medial temporal lobe has performed this function, why should additional, diencephalic nuclei be required for the same cognitive task?…”
Section: Toward a Model Of Diencephalic Contributions To Recognition mentioning
confidence: 99%
See 1 more Smart Citation
“…A similar controversy exists over the findings from functional imaging studies. Different studies have shown either recollection-specific activation of the hippocampus 8 or activation that occurs more generally in medial temporal lobe areas associated with the strength of memory 9 .…”
mentioning
confidence: 99%
“…In this context, recollection can be defined as memory for an event with retrieval of accompanying spatiotemporal contextual details, whereas familiarity does not involve this degree of episodic richness (Tulving 1985;Aggleton and Brown 2006). It has been proposed that recollection is mediated by the hippocampus; by contrast, familiarity is thought to be subserved by the perirhinal cortex (Brown and Aggleton 2001;Aggleton and Brown 2006;Eichenbaum et al 2007; but see Squire et al 2007 for a conflicting view). The basis of this neuroanatomical distinction is largely predicated upon a series of hippocampal amnesic cases in which familiarity processes are relatively spared in the context of recollection deficits (e.g.…”
mentioning
confidence: 99%